Taṭwīr Kitāb “Ayo Belajar Bahasa Arab Untuk MI Kelas IV” Bi Barnāmij al-`Arūḍ at-Taqdīmiyyah Bi SDIT Quantum School - Lilis Putri Sari; Mukhlisah Mukhlisah (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2021)
The development of method is research that conducted to produce the specific product. Textbook is the prominent sources to attract student’s attention. The content of the grammer in the textbook makes a students bored and lack of enthusias in Arabic lesson. Therefore then the researcher developed the textbook in the composition of the powerpoint, to support the bold reform steps in the installation. For this purpose, this research aims at learning how to develop a textbook “Ayo Belajar Bahasa Arab untuk MI kelas IV” as well to find out the effectiveness of the product from the development of this book. The approach adopted by the researcher in this research thesis is the methodology of the scientific research and development (Research & Development R & D). The data collection consist of direct observation, test and questionnaire in the fourth grade students. The Arabic book has been development with the following steps: potential and issues, data collection, production design, certivication production with the expert in teaching and learning, improvement of production, sampling of production in the sall group, improvement of production. The use of books that have been developed with powerpoint is effective to improve students understanding in learning Arabic.